2020
DOI: 10.1111/jdi.13313
|View full text |Cite
|
Sign up to set email alerts
|

Corneal nerve loss in children with type 1 diabetes mellitus without retinopathy or microalbuminuria

Abstract: Aims/Introduction Corneal confocal microscopy is a rapid, non‐invasive ophthalmic technique to identify subclinical neuropathy. The aim of this study was to quantify corneal nerve morphology in children with type 1 diabetes mellitus compared with age‐matched healthy controls using corneal confocal microscopy. Materials and Methods A total of 20 participants with type 1 diabetes mellitus (age 14 ± 2 years, diabetes duration 4.08 ± 2.91 years, glycated hemoglobin 9.3 ± 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…This study shows a signi cant reduction in central corneal nerve bre parameters in obese subjects with and without diabetes, in agreement with our previously published studies in subjects with obesity [13,23] and diabetes [5,24]. We now further report greater corneal nerve damage in the more distal inferior whorl compared to the central region providing support for a dying-back neuropathy, consistent with studies in adults [25,26] and children [27] with diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…This study shows a signi cant reduction in central corneal nerve bre parameters in obese subjects with and without diabetes, in agreement with our previously published studies in subjects with obesity [13,23] and diabetes [5,24]. We now further report greater corneal nerve damage in the more distal inferior whorl compared to the central region providing support for a dying-back neuropathy, consistent with studies in adults [25,26] and children [27] with diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…Knowing that neuropathy is a known complication associated with T1DM and CD, and that a possible bidirectional crosstalk linking the gut microbiota with the nervous system has been previously described [ 22 ], we wanted to test whether the gut microbes identified in this study were correlated with corneal neuropathy. We have shown that CCM demonstrates evidence of neuropathy in these children with T1DM [ 38 ] and to a lesser extent in those with CD [ 39 ]. We performed a linear regression to determine any possible association between the abundance of the gut microbiota and abnormal corneal nerve fiber length (CNFL) ( Supplementary Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using the Heidelberg Retina Tomograph Cornea Module (Heidelberg Engineering, Vista, CA, USA), participants underwent corneal confocal microscopy as per an established protocol [ 38 ]. Briefly, one eye was randomly selected and anaesthetized with a drop of Alcaine (proparacaine hydrochloride 0.5%; Alcon, Mississauga, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, researchers reported a high sensitivity and specificity in using CCM measurements to assess type 1 diabetic peripheral neuropathy 39,40 , as well as in patients with prediabetes 41 and even children with type 1 diabetes 42 . In the present study, it is feasible to evaluate type 2 diabetes mellitus-related chronic complications by using CCM measurements, especially CNFL, but the sensitivity and specificity still need to be improved, which might be related to CCM image acquisition, automatic analysis software and slight diabetic complications in this study.…”
Section: Discussionmentioning
confidence: 99%